Diseminasi Budidaya Biota Laut sebagai Upaya Peningkatan Pendapatan Masyarakat di Kabupaten Banyuasin, Sumatera Selatan - Riris Aryawati; Tengku Zia Ulqodri; Muhammad Hendri; Anna Ida Sunaryo Purwiyanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity was designed to address the economic challenges faced by fishermen in Sungsang II Village, Banyuasin II Regency, South Sumatra Province. Fishermen are often disrupted by weather conditions, such as the west monsoon or rainy season, which limit fishing activities and negatively impact their income. This program involved 48 fishermen and two partners, intending to increase the knowledge and creativity of the participants regarding alternative fisheries. The presentation covered aquaculture knowledge and the various organisms involved in it. In-depth explanations were also provided on silvofishery and aquaponics methods as alternatives to enhance income. Additionally, this activity highlighted potential local organisms that could serve as cultivation species. The program was carried out in several stages: preparation, implementation, monitoring, and evaluation. The evaluation was conducted to assess the success of the dissemination based on participants’ enthusiasm and the increase in knowledge gained. The results indicated that the program successfully achieved its intended objectives, evidenced by the participants' enthusiasm and a 45% increase in their understanding. However, the skepticism of some participants and limited capital for cultivation posed challenges to the dissemination process. The community's interest in and understanding of the introduced cultivation methods form the basis for the future, particularly focusing on silvofishery and aquaponics techniques. Recommendations for applying these cultivation methods will be formulated as follow-up steps to ensure the sustainability and positive impact of this initiative. Through this approach, it is hoped that the community can attain greater economic stability and enhanced environmental sustainability.